2016
DOI: 10.1093/bioinformatics/btw494
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous gene finding in multiple genomes

Abstract: The method is implemented in C ++ as part of Augustus and available open source at http://bioinf.uni-greifswald.de/augustus/ CONTACT: stefaniekoenig@ymail.com or mario.stanke@uni-greifswald.deSupplementary information: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Trimmed reads were mapped to the corresponding genome assembly using HISAT2 v2.0.4 ( Kim et al, 2015 ) specifying a max intron length of 5 kb and the “dta-cufflinks” option to report alignments tailored for cufflinks input. Cufflinks-guided annotations were generated using CodingQuarry pathogen-mode (CQPM, Testa et al, 2015 ) which were later provided to Augustus ( Stanke et al, 2006 ; König et al, 2016 ) as hints. Intron position hints were extracted from the mapped RNAseq reads using the bam2hints utility provided with Augustus and position hints from PTR Pt-1C-BFP proteins (assembly ASM14998v1) mapped to each genome using Exonerate v2.2.0 ( Slater and Birney, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Trimmed reads were mapped to the corresponding genome assembly using HISAT2 v2.0.4 ( Kim et al, 2015 ) specifying a max intron length of 5 kb and the “dta-cufflinks” option to report alignments tailored for cufflinks input. Cufflinks-guided annotations were generated using CodingQuarry pathogen-mode (CQPM, Testa et al, 2015 ) which were later provided to Augustus ( Stanke et al, 2006 ; König et al, 2016 ) as hints. Intron position hints were extracted from the mapped RNAseq reads using the bam2hints utility provided with Augustus and position hints from PTR Pt-1C-BFP proteins (assembly ASM14998v1) mapped to each genome using Exonerate v2.2.0 ( Slater and Birney, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Species with an overlapping ORF longer than 50% of the D. melanogaster ORF were denoted as ORF harbouring. To generate a set of syntenic ORFs for evolutionary rate analysis, the same methodology was applied to a twelve-way whole genome alignment of the Drosophila clade (König et al 2016). In this case, the syntenic regions corresponding to all Drosophila single exon orphan genes, old genes and intergenic ORFs in the study set were extracted and syntenic ORFs were identified as before.…”
Section: Analysis Of Syntenic Genomic Regionsmentioning
confidence: 99%
“…Complementing direct evidence from transcriptional and translational data, comparative genomics allows finding functional genomic elements that are conserved between species. Genes, exons, and other DNA elements under natural selection are often highly conserved between close relatives and the core set of human genes are conserved in all bilateria …”
Section: Evidence For Protein‐coding Genes Comes From Multiple Sourcesmentioning
confidence: 99%